School,Reform and Society in the New Russia - Webber, S. author. aut Link
XX, 252 p.
Keywords: The Russian school system should have an important role to play in the process of democratisation and the revival and modernisation of the economy in that country. Is it in a position to respond to this task? In this book an analysis is conducted of the attempts to reform the Russian school system in the 1990s, setting the progress made and problems encountered by the schools against the broader context of political, economical and social flux in Russia as a whole.